Climbers and Lianas Distribution in Jharkhand forests - Kumar, Amit; Prasad, Santosh; Singh, Sanjay (Indian Forester, 2013)
The present study mainly focuses on the documentation of lianas and climbers in different forest habitat of five districts of Jharkhand viz., Ranchi, East-Singhbhum, Hazaribagh, Chatra, and Latehar during the year 2009-2012. A total of 45 important climbers including 7 lianas were identified and thoroughly observed during study period in which family Fabaceae represented dominant group followed by Cucurbitaceae, Dioscoraceae and Liliaceae.